Breast fibromatosis mimicking breast carcinoma - Ha, Kelli Y. (Baylor Health Care System, 2013)
Fibromatosis arising from the breast, also referred to as desmoid tumor, aggressive fibromatosis, or low-grade fibrosarcoma, is a rare benign entity, accounting for only 0.2% of all breast tumors. Associations with familial multicentric fibromatosis and trauma, including that resulting from surgical intervention, have been reported. Awareness of this lesion is important, as the diagnosis has often been confused with that of breast carcinoma. We present the case of a 30-year-old white woman who presented with a palpable mass within the medial portion of her right breast. She reported breast carcinoma in both her paternal grandmother and maternal aunt. Subsequent mammographic and sonographic evaluation demonstrated an irregular solid mass within the posteromedial portion of the right breast. Ultrasound-guided core needle biopsy revealed low-grade myofibroblastic proliferation consistent with breast fibromatosis. The lesion was surgically resected via wide local excision. Follow-up mammograms performed 1 and 2 years after resection demonstrated no radiographic evidence of recurrence.